Klippel–Trénaunay Syndrome and Developmental Coxa Vara in the Same Limb: A Case Report with a Review of the Literature - Zacharia, Balaji; Alex, Jittu; Rajmohan, Ashwin (International Journal of Angiology, 2021)
We present a case of a 14-year-old girl who was first treated when she was 4 years old. She had progressive limping of the left lower limb from the age of 3 years. She was diagnosed to have developmental coxa vara of the left hip and treated by a subtrochanteric valgus osteotomy of the left femur. Later, she developed hypertrophy of the left upper and lower limbs. There were port-wine stains over the left lower limbs with multiple superficial varicosities. Her diagnosis was Klippel–Trénaunay syndrome (KTS). She is asymptomatic at the final follow-up. Both developmental coxa vara and KTS are rare conditions. We present this case to demonstrate the rarest combination of two rare conditions occurring in the same limb.
Keywords: Klippel–Trénaunay syndrome; developmental coxa vara; hypertrophy of limb; port-wine stain